Virulence Properties of mcr-1-Positive Escherichia coli Isolated from Retail Poultry Meat - Michaela Kubelová; Ivana Koláčková; Tereza Gelbíčová; Martina Florianová; Alžběta Kalová; Renáta Karpíšková (Microorganisms, 2021)
The great plasticity and diversity of the Escherichia coli genome, together with the ubiquitous occurrence, make E. coli a bacterium of world-wide concern. Of particular interest are pathogenic strains and strains harboring antimicrobial resistance genes. Overlapping virulence-associated traits between avian-source E. coli and human extraintestinal pathogenic E. coli (ExPEC) suggest zoonotic potential and safety threat of poultry food products. We analyzed whole-genome sequencing (WGS) data of 46 mcr-1-positive E. coli strains isolated from retail raw meat purchased in the Czech Republic. The investigated strains were characterized by their phylogroup—B1 (43%), A (30%), D (11%), E (7%), F (4%), B2 (2%), C (2%), MLST type, and serotype. A total of 30 multilocus sequence types (STs), of which ST744 was the most common (11%), were identified, with O8 and O89 as the most prevalent serogroups. Using the VirulenceFinder tool, 3 to 26 virulence genes were detected in the examined strains and a total of 7 (15%) strains met the pathogenic criteria for ExPEC. Four strains were defined as UPEC (9%) and 18 (39%) E. coli strains could be classified as APEC. The WGS methods and available on-line tools for their evaluation enable a comprehensive approach to the diagnosis of virulent properties of E. coli strains and represent a suitable and comfortable platform for their detection. Our results show that poultry meat may serve as an important reservoir of strains carrying both virulence and antibiotic resistance genes for animal and human populations.